PENGEMBANGAN BUKU EVALUASI TEKA-TEKI SILANG IPAS KELAS V SEMESTER 1 SEKOLAH DASAR - sarasevo, Helen; M.Yusuf Setia Wardana; Intan Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
HELEN SARASEVO NPM 22120295. "Development of a Crossword Puzzle Evaluation Book for 5th Grade Science Students, Semester 1 of Elementary School." Thesis. Elementary School Study Program. Faculty of Education, Universitas PGRI Semarang. Supervisor 1: M. Yusuf Setia Wardhana, S.Pd., M.Pd. and Supervisor 2: Intan Rahmawati, S.Pd., M.Pd. This research was motivated by the initial problems identified: the use of multiple-choice and short-answer questions for science learning evaluation, student boredom and lack of enthusiasm, and students' preference for crossword puzzles in science learning evaluation. The purpose of this study was to determine whether the "Development of an Evaluation Book for Science Crossword Puzzles for Grade 5, Semester 1 of Elementary School" is valid and practical for use in evaluating science learning, especially in grade 5 of elementary school. The type of research used is R&D (Research and Development) with the ADDIE model, namely Analysis, Design, Development, Implementation, and Evaluation. This research was conducted at SD N 01 Limpung. The subjects of this study were 16 grade 5 students of SD N 01 Limpung. The validation results by material validation experts by lecturers were 84.2%, media validation experts 95.7%, practitioner validation experts 98.3%, and student responses received 91.3%. The conclusion of the study "Development of an Evaluation Book for Science Crossword Puzzles for Grade 5, Semester 1 of Elementary School" is valid and practical because it has achieved the criteria score "very good". Suggestions for developing the 5th-grade, 1st-semester Elementary School Science crossword puzzle evaluation book include further in-depth material and sub-chapters to cover more material and potentially expand it into a digital format. Keywords: Learning Media, Science, Evaluation, Crossword Puzzles.